Data from: New perspectives on frontal variability in the southern ocean - Chapman, Christopher C. (Dryad Digital Repository, 2017)
The frontal structure of the Southern Ocean is investigated using the Wavelet/Higher Order Statistics Enhancement (WHOSE) frontal detection method, introduced in Chapman (2014). This methodology is applied to 21 years of daily gridded absolute dynamic topography (ADT) data to obtain daily maps of the locations of the fronts. By forming frontal occurrence frequency maps and then approximating these occurrence-maps by a superposition of simple functions, the time-mean locations of the fronts, as well as a measure of their capacity to meander, are obtained and related to the frontal locations found by previous studies. The spatial and temporal variability of the frontal structure is then considered. The number of fronts is found to be highly variable throughout the Southern Ocean, increasing (‘splitting’) downstream of large bathymetric features and decreasing (‘merging’) in regions where the fronts are tightly controlled by the underlying topography. These splitting/merging events are related to changes in the underlying frontal structure whereby regions of high frontal occurrence cross or spread over streamfunction contours. In contrast to the number of fronts, frontal meandering remains relatively constant throughout the Southern Ocean. Little to no migration of the fronts over the 1993-2014 time period is found, and there is only weak sensitivity of frontal positions to atmospheric forcing related to the Southern Annular Mode or the El Niño Southern Oscillation. Finally, the implications of these results for the study of cross-stream tracer transport is discussed. ssh_front_climatology_1993Southern Ocean front locations obtained from AVISO gridded SSH using the WHOSE method.ssh_front_locations_1993.ncssh_front_locations_1994Southern Ocean front locations obtained from AVISO gridded SSH using the WHOSE method.SSH front locations 1995Southern Ocean front locations obtained from AVISO gridded SSH using the WHOSE method.ssh_front_locations_1995.ncSSH front locations 1996Southern Ocean front locations obtained from ...